2020
DOI: 10.1051/0004-6361/202037815
|View full text |Cite
|
Sign up to set email alerts
|

The role of Galactic H II regions in the formation of filaments

Abstract: Context. Massive stars and their associated ionized (H II) regions could play a key role in the formation and evolution of filaments that host star formation. However, the properties of filaments that interact with H II regions are still poorly known. Aims. To investigate the impact of H II regions on the formation of filaments, we imaged the Galactic H II region RCW 120 and its surroundings where active star formation takes place and where the role of ionization feedback on the star formation process has alre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 57 publications
5
21
0
Order By: Relevance
“…The crests traced by DisPerSE may correspond to "filament-crests" or to "shellcrests" associated with shell-like structures around H II regions (such as those around sources II and IV). We mention briefly possible differences between "filament-crests" and "shell-crests" below (see also Zavagno et al 2020, who present a study of the properties of shell-crests and filament-crests in the RCW 120 H II region).…”
Section: Properties Of the Different Crests Identified Towards The Ngmentioning
confidence: 99%
“…The crests traced by DisPerSE may correspond to "filament-crests" or to "shellcrests" associated with shell-like structures around H II regions (such as those around sources II and IV). We mention briefly possible differences between "filament-crests" and "shell-crests" below (see also Zavagno et al 2020, who present a study of the properties of shell-crests and filament-crests in the RCW 120 H II region).…”
Section: Properties Of the Different Crests Identified Towards The Ngmentioning
confidence: 99%
“…Therefore, conclusions from this model, even if it supports the idea of triggered star formation, must be taken with caution. Detailed analysis of the interplay between the H II region and the PDR (Tremblin et al 2014;Figueira et al 2018;Zavagno et al 2020) might be a better indicator but are also not exempt from some uncertainties (Dale et al 2015) regarding induced star formation.…”
Section: Collect and Collapse Mechanismmentioning
confidence: 99%
“…RCW 120 is a well-studied Galactic H II region because of its ovoid shape and its relatively close distance (1.34 kpc, Russeil 2003;Zavagno et al 2007). Thanks to these advantages, this region has received a lot of attention from observers and simulations, and has been studied in several papers (Zavagno et al 2007(Zavagno et al , 2010(Zavagno et al , 2020Deharveng et al 2009;Anderson et al 2012Anderson et al , 2015Tremblin et al 2014;Kirsanova et al 2014Kirsanova et al , 2019Torii et al 2015;Walch et al 2015;Mackey et al 2016;Figueira et al 2017Figueira et al , 2018Marsh & Whitworth 2019). Figueira et al (2017) showed that two clumps observed at millimeter wavelength host different kinds of sources with respect to their evolutionary stage.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, it is not clear whether this turbulence increment could change a fragmentation from thermal-dominated to turbulentdominated. The fragmentation at 0.01 pc scale in the most massive star-forming clump (M ∼ 4) impacted by the H ii region RCW 120 (Kirsanova et al 2019;Zavagno et al 2020) is investigated by Figueira et al (2018) and they suggested that turbulent fragmentation is dominant due to the H ii region feedback. Even for the cases where the fragmentation at around 0.02 pc scale in the clumps is still thermal-dominated under the vigorous feedback of H ii regions, the fragments could be more massive or less numerous (Liu et al 2017).…”
Section: Transition Of Fragmentation Mechanismmentioning
confidence: 99%